2017
DOI: 10.1007/s10811-017-1169-4
|View full text |Cite
|
Sign up to set email alerts
|

Variation in growth, yield and protein concentration in Saccharina latissima (Laminariales, Phaeophyceae) cultivated with different wave and current exposures in the Faroe Islands

Abstract: Ropes seeded directly with Saccharina latissima were deployed at different exposures (sheltered, current exposed and wave exposed) in a Faroese sound and characteristics of growth and quality of the biomass and surroundings were evaluated during the growth season from March to August 2015. Saccharina latissima individuals cultivated at the current exposed location were heavier compared to the individuals cultivated at the other locations; however, the total biomass yield was significantly lower at the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 26 publications
6
26
3
Order By: Relevance
“…Nutritional value and food safety The N concentrations observed in the S. latissima biomass were in agreement with values reported in the literature for this species at this time of the year (Nielsen et al 2014;Bruhn et al 2016;Mols-Mortensen et al 2017), and the estimated protein content of the sugar kelp product did not significantly change in the processes of heat-treatment and fermentation. A specific analysis of the amino acid composition of the biomass would be needed in order to fully evaluate the effects of the heattreatment and fermentation processes on the nutritional value of the final product (Mols-Mortensen et al 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Nutritional value and food safety The N concentrations observed in the S. latissima biomass were in agreement with values reported in the literature for this species at this time of the year (Nielsen et al 2014;Bruhn et al 2016;Mols-Mortensen et al 2017), and the estimated protein content of the sugar kelp product did not significantly change in the processes of heat-treatment and fermentation. A specific analysis of the amino acid composition of the biomass would be needed in order to fully evaluate the effects of the heattreatment and fermentation processes on the nutritional value of the final product (Mols-Mortensen et al 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Protein content was higher at high than at low latitudes throughout the cultivation period, following the latitudinal pattern in ambient nitrate fluctuation (Harnedy and FitzGerald 2011). Seasonally, the protein contents were higher by a factor of 3 in spring than in summer, which is in agreement with a 4-to 8-fold difference in protein content found for S. latissima between winter/spring and summer in Denmark and the Faroe Islands (Marinho et al 2015a;Mols-Mortensen et al 2017). In contrast, there was not found significant correlation between protein content and season in another experiment from the Faroe Islands, most likely the result of smaller seasonal fluctuation in nutrients (Bak et al 2019).…”
Section: Discussionsupporting
confidence: 76%
“…Growth performance The frond length and biomass yield peaked 5 and 8 weeks later in the northern (9-69°N) than in the central (6-63°N) and southern (1-58°N) locations, respectively, likely because of seasonal differences in temperature, daylight and an earlier depletion of ambient inorganic nutrients by phytoplankton blooms in the low than high latitudes (Rey et al 2007;Ibrahim et al 2014). Maximum frond length and biomass yield were greatest at central (6-63°N, in summer) and northern (9-69°N, in autumn) locations, with levels comparable to S. latissima previously cultivated in Norway (Handå et al 2013;Fossberg et al 2018;Forbord et al 2019;Matsson et al 2019) and as high as or higher than several cultivation trials across Europe under variable conditions (Peteiro et al 2014;Mols-Mortensen et al 2017;Bak et al 2018). The maximum yield of 14 kg m −1 found in our study is far lower than registered for other cultivated kelp species like Macrocystis pyrifera in Chile (up to 22 kg m −1 ) (Macchiavello et al 2010) and hybrids of Undaria pinnatifida and Undariopsis peterseniana in Korea (37.5 kg m −1 ) (Hwang et al 2012) due to both morphology/individual biomass potential and breeding strategies.…”
Section: Discussionmentioning
confidence: 87%
“…The overall best performance of all measured variables was obtained by seeding twine with spores and pre-cultivating them in the hatchery for 42 days (S42), a treatment used in previous experiments in Norway (Forbord et al 2012;Handå et al 2013;Fossberg et al 2018;Sharma et al 2018). Frond lengths in June for the S42 treatment were comparable to those of previous experiments in the Faroe Island and Norway (Handå et al 2013;Mols-Mortensen et al 2017;Bak et al 2018), and the biomass was well within the range found by other trials in Europe (Peteiro and Freire 2009;Kraan 2013;Mols-Mortensen et al 2017;Matsson et al 2019). The D35 treatment, on the contrary, showed the shortest frond lengths and the lowest biomass yield, which was in the same range or higher as found in several Danish cultivation experiments Fig.…”
Section: Growth Performance At Seasupporting
confidence: 58%
“…This method can be advantageous as the use of incubation facilities might be shortened by several weeks or, in the case of direct seeding, omitted completely. The use of a binder to attach spores, gametophytes or sporophytes to the substrate is preferred by several commercial farmers and in research projects (Mols-Mortensen et al 2017;Bak et al 2018;Kerrison et al 2018Kerrison et al , 2019. Recent experiments have shown that a binder method of cultivation is not only as effective as traditional methods but also can be 100 times more space-efficient during the laboratory phase (Kerrison et al 2018).…”
Section: Introductionmentioning
confidence: 99%